2013
DOI: 10.11648/j.acm.20130204.12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cracked Plates Using Localized Multi¬Domain Differential Quadrature Method

Abstract: In this paper, A multi-domain differential quadrature method is employed to solve a mode III crack problem. The domain of the problem is assumed to be irregular rather than it possesses discontinuities, (cracks). The entire domain is divided into several subdomains, according to the crack locations. A conformal mapping is applied to transform the irregular subdomains to regular ones. Then the differential quadrature method is employed to solve the problem over the transformed domains. Further, it's focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To ensure the validity of proposed scheme, the obtained results are compared with previous ones for cracked and un-cracked Euler-Bernoulli and Timoshenko problems. A quadrature numerical scheme is designed to solve cracked Euler-Bernoulli beam problems, equations (22)(23)(24)(25)(26)(27)(28)(29). For each sub-beam, N is to be varied from 5-50 to determine N leading to accurate convergent results.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the validity of proposed scheme, the obtained results are compared with previous ones for cracked and un-cracked Euler-Bernoulli and Timoshenko problems. A quadrature numerical scheme is designed to solve cracked Euler-Bernoulli beam problems, equations (22)(23)(24)(25)(26)(27)(28)(29). For each sub-beam, N is to be varied from 5-50 to determine N leading to accurate convergent results.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Recently, differential quadrature method is introduced as promising numerical technique. This method leads to very accurate results by using small number of nodal points [23][24][25][26]. Rotational spring model is employed to simulate the crack existence.…”
Section: Introductionmentioning
confidence: 99%
“…Lagrange interpolation polynomials, the cardinal sine function, the delta Lagrange kernel (DLK), and the regularized Shannon kernel (RSK) are some examples of such functions which have led to the development of the polynomial-based differential quadrature method (PDQM) [21], the sinc differential quadrature method (SDQM) [22], and the discrete singular convolution differential quadrature method (DSCDQM), respectively [23]. Thus, the DQ method has emerged as a powerful numerical discretization tool for solving a variety of problems in the engineering and physical sciences [24][25][26][27][28][29][30]. Bellman et al [19] suggested that the nth-order derivative of the function with respect to a grid point can be approximated as a linear summation of the values of the function for all of the sample points in the domain.…”
Section: Introductionmentioning
confidence: 99%